COVID-19 vaccination induces cross-reactive dengue virus antibodies with altered isotype profiles and in vitro antibody-dependent enhancement - Reinig, Sebastian; Kuo, Chin; Huang, Sheng-Yu; Hsiung, Kuei-Ching; Chen, Po-Kai; Ito, Etsuro; Lee, Ing-Kit; Tsai, Ching-Yen; Lin, Shu-Min; Shih, Shin-Ru (Frontiers in Immunology, 2025)
BackgroundSARS-CoV-2 infection and COVID-19 vaccination can induce antibodies that cross-react with dengue virus (DENV). Pre-existing IgG antibodies against DENV are known to enhance infection through antibody-dependent enhancement (ADE) via Fcγ receptors. COVID-19 vaccines induce an altered IgG subclass distribution with modified Fcγ receptor affinity. This study investigates the isotype profile of DENV cross-reactive antibodies induced by COVID-19 vaccination and their potential to mediate ADE.MethodsWe retrospectively collected 271 serum samples from individuals in Taiwan who were either SARS-CoV-2-unvaccinated, vaccinated with 1–3 doses of COVID-19 vaccine, recipients of an Omicron-era booster, or previously recovered from dengue infection. Antibody titers (IgM, IgA, and IgG subclasses 1–4) against SARS-CoV-2 spike (S) glycoprotein and DENV serotype 2 envelope (E) protein were measured by enzyme-linked immunosorbent assay (ELISA). Selective depletion of anti-S or anti-E antibodies was performed to confirm cross-reactivity. ADE activity was assessed in vitro by incubating DENV-2 particles with serum antibodies followed by infection of Fcγ receptor-bearing THP-1 monocytic cells.ResultsCross-reactive anti-E antibodies in COVID-19-vaccinated individuals were predominantly IgM and IgA, whereas anti-S antibodies in vaccinated individuals and anti-E antibodies in dengue-recovered patients were dominated by IgG1. Low levels of cross-reactive anti-E IgG detected in vaccinated individuals were mainly of the low-affinity IgG2 and IgG4 subclasses. These vaccine-induced cross-reactive antibodies mediated significantly stronger in vitro ADE compared with antibodies from natural DENV infection, particularly after the first or second vaccine dose and after Omicron-variant boosters. Inactivation of complement reduced ADE in COVID-19-vaccinated sera but enhanced it in sera from dengue-recovered individuals.ConclusionCOVID-19 vaccination induces DENV cross-reactive antibodies with a distinct isotype profile and distinct ADE compared with natural dengue infection. Due to low Fc-affinity these antibodies likely do not pose a threat of dengue. These findings highlight the importance of considering off-target immunity and ADE risk in future vaccine design.